Development of a high specificity typing method for the detection of herpes simplex virus - Chen, Zhu; Zhao, Kaixuan; Tan, Boyu; Tong, Zengrui; He, Ziyu; Luo, Xiaofang; Cai, Lei; Wang, Hanming; Leung, Polly H. M.; Chow, Franklin Wang-Ngai; Chen, Hui; Deng, Yan (Frontiers in Bioengineering and Biotechnology, 2022)
Herpes disease is caused by Herpes simplex virus (HSV). It has become one of the global health problems. This paper reports a method for HSV type testing. First specific primers sequence for HSV-1 and HSV-2 were selected, designed, and synthesized. Then, these amplification products were proved by sequencing and analysis. Lastly, we optimized the reaction system and PCR reaction program by orthogonal design and sensitivity testing. Results showed that the lowest concentration in HSV-type testing is about 6.67×106 copies/mL. Moreover, the specificity of detection was very high. So, this method has very great potentials for HSV type testing in clinical practice.